PENGARUH JENIS AGREGAT KASAR TERHADAP KUAT TEKAN BETON POROUS - Yunus Lubis; Yudha Hanova; Ricky Bakara; Rahmat Digantara (Jurnal Teknik Sipil, 2026)
Porous concrete is a type of lightweight concrete that has interconnected cavities or pores that allow water to seep through the concrete surface. These characteristics make porous concrete widely used in environmentally friendly construction, such as road paving, sidewalks, and parking areas that require a natural drainage system. One important factor that influences the quality of porous concrete is the type of coarse aggregate used, because the physical properties and size of the aggregate grains directly affect the porosity and compressive strength of the concrete. This study aims to determine the effect of varying the type of coarse aggregate on the compressive strength of porous concrete. The aggregates used consist of several types, namely crushed stone and natural gravel with certain gradations. The research method is carried out by mixing aggregate, cement, and water according to the specified ratio, then molding cylindrical test specimens and conducting compressive strength tests at certain ages. The results show that varying the type of coarse aggregate makes a significant difference in the compressive strength of porous concrete. Porous concrete with crushed stone aggregate tends to have higher compressive strength than that with natural gravel aggregate, because the rough surface of the crushed stone produces a better bond with the cement paste. Thus, the selection of the type of coarse aggregate is very influential in producing porous concrete with optimal strength.